Troubleshooting Scleral Contact Lens Deposits: A Case Study - Nikit Kundra; Sonali Gupta; Gagan Sahni; Renu thakur (Pakistan Journal of Ophthalmology, 2025)
Scleral contact lenses are extensively used in clinical practices; however, deposits on scleral lenses are still a prevalent problem among wearers.The current case presents an innovative method of troubleshooting scleral lens deposit.A 31-year-old Asian male,using scleral lens from past six years, presented with complaints of irritation and decreased vision due to heavy lens deposits. A novel in-office deep cleaning procedure was carried out using a specially created manual technique with a specific cleaning solution to break up the surface deposits without damaging lens. After cleaning, the patient demonstrated better visual acuity, less discomfort, and long wearing time.A low-cost innovative cleaning technique can effectively increase life of scleral lens and improve patient comfort.